Development and Characterization of a Curcumin-Loaded Alginate-Xanthan Gum Hydrogel for Antibacterial Activity and Controlled Drug Release - Torres-Ayala, L.; Cespedes, S.; Kim, S.; Nakamatsu, J.; Obregón Príncipe, M.; Castillo, D. (Trans Tech Publications Ltd, 2025)
This article describes the development and characterization of a curcumin-loaded alginate-xanthan gum hydrogel, designed to provide both antibacterial activity and controlled drug release.The hydrogel formulation consisted of 4% (w/v) alginate, 4% (w/v) xanthan gum, and 500 μg/mL of curcumin. Sterilization was achieved through ethanol immersion, UV irradiation, and autoclaving, with the latter two methods proving to be the most effective in maintaining long-term sterility. Antibacterial efficacy was tested against Staphylococcus aureus, demonstrating a significant inhibition zone around the hydrogel. The curcumin release profile indicated a sustained release over 72 hours, suggesting its suitability for prolonged antibacterial applications.
Keywords: Antibacterial activity; Xanthan gum; Curcumin; Sterilization (economics); Drug; Antibacterial agent; Staphylococcus aureus; https://purl.org/pe-repo/ocde/ford#3.01.04